Improving hardiness in elite rugby players - Thompson, C. (Victoria University, 2017)
Researchers in sport (Sheard & Golby, 2010) and other performance domains (Florian, Mikulincer, & Taubman, 1995) have identified hardiness as a personality characteristic that contributes to performance by differentiating the way individuals respond to stressors they face. The purpose of this study was to investigate how an applied psychology intervention to improve hardiness would affect the way athletes coped with stressors in their elite sport environment. In this qualitative study, I used a case study design consisting of an initial interview session followed by a further five intervention sessions, based on cognitive behavioural therapy. The participants were two first-year professional rugby players at an elite club in a top level national competition. I present each case as a separate story detailing the identification of sources of stress experienced by each player, the process of the hardiness intervention to address those sources of stress, and the outcomes for the participants. The analysis confirmed the effect of the players` `hardy attitudes` on stress. Results showed specific examples of how hardiness facets related to performance and subjective experience. In both cases the Commitment and Control facets of hardiness showed greater change than the Challenge facet. Threats from competitive `on-field` stressors proved more manageable than relationship-based threats. Based on the findings from the study, I question the fit of the Challenge dimension within Kobasa`s (1981) model of hardiness, and the degree to which the facet is amenable to change within a short-term intervention. Although this study was limited to two case studies, I identified interpersonal factors relevant to the hardiness construct that interacted strongly with hardiness facets in determining subjective responses to stress.